PENGARUH PEMERIKSAAN PAJAK, KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Pada KPP Pratama Malang Utara) - Nur Aini Eka Putri; Nur Diana; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis research was conducted to determine the effect of tax audits, taxpayer awareness, service quality on the level of individual taxpayer compliance at the North Malang Tax Service Office (KPP). The analysis method used is multiple linear regression. The data used in this study are primary data. Data collection techniques in this study using purposive sampling. The test used in this study is the f test, R2 test, and t test. Based on the results of the tests that have been carried out, it is concluded that simultaneously the tax audit variable, taxpayer awareness, service quality has a significant and simultaneous effect on individual taxpayer compliance. The partial test results show that the tax audit variable and taxpayer awareness partially have a positive effect on the level of individual taxpayer compliance at the North Malang Tax Office. Meanwhile, partially service quality has no effect on individual taxpayer compliance.Keywords: tax audit, taxpayer awareness, service quality, taxpayer compliance